THE ROLE OF COMMUNITY EMPOWERMENT CARRIED OUT BY VILLAGE GOVERNMENT IN THE REGIONAL AUTONOMY ERA - Agustina, Enny (Universitas Kuningan, 2019)
Realizing prosperity in the community needs to be supported by a good development management. In the governance system, it is necessary to have governance behaviour that is honest, open, responsible and democratic. In the community structure, a mechanism providing opportunities for the community in the decision-making process for public interests needs to be developed. This study discusses the role of the village head in empowering village communities. This study used a community-based approach so that the community knows in detail concerning the role of the village head in the Framework for the Implementation of Village Autonomy based on Law No. 6 of 2014 concerning Village. The results showed that village head must have a fair and wise attitude in carrying out his duties and obligations. Besides, the village head must give an easy access to the community in providing assistances. Yet, the most important thing is that, as a leader, the village head must be able to provide a good example for their subordinates so as to create maximum results and good community environment.Â Mewujudkan kesejahteraan di masyarakat, perlu didukung oleh manajemen pembangunan yang baik. Dalam tatanan tata pemerintahan, perlu untuk memiliki perilaku tata kelola yang jujur, terbuka, bertanggung jawab dan demokratis, sementara dalam tatanan masyarakat suatu mekanisme perlu dikembangkan yang memberikan peluang bagi masyarakat dalam proses pengambilan keputusan untuk kepentingan bersama. studi ini membahas bagaimana peran kepala desa dalam memberdayakan masyarakat pedesaan. Penelitian ini menggunakan metode pendekatan kepada masyarakat sehingga masyarakat tahu lebih detail tentang Peran Kepala Desa dalam Kerangka Pelaksanaan Otonomi Desa Menurut Undang-Undang Nomor 6 tahun 2014 tentang Desa. Hasil penelitian ini yaitu dalam melaksanakan tugas dan kewajiban Kepala Desa mereka harus mempunyai tingkah laku yang adil, bijaksana dan tidak mempersulit dalam memberikan layanan kepada semua masyarakat. Namun yang lebih penting lagi bahwa sebagai seorang pemimpin harus bisa memberikan contoh untuk bawahan sehingga mendapatkan hasil yang maksimal dan terciptanya persatuan komunitas yang baik.